PENINGKATAN KETERAMPILAN BERPIKIR KRITIS MELALUI MODEL INKUIRI BERBANTUAN MEDIA KONKRET PADA SISWA KELAS 5 SD NEGERI MANGUNSARI 05 TAHUN PELAJARAN 2018/2019 - Indriyani, Dina; Mawardi, Mawardi; Wardani, Krisma Widi (Jurnal Basicedu, 2019)
This research aims to improve the critical thinking skills of 5th grade students of SD Negeri Mangunsari 05 in the school year 2018/2019, and to implement the steps of the inquiry learning model in 5th grade. This type of research is classroom action research. To collect the data I use non-technical tests include observation, questionnaires, and documentation. Critical thinking skills in the preliminary study showed that from 40 students there was a percentage of 38% in the very high category, 25% in the high category and 37% in the low category. The result of cycle I showed that 20% are in a very high category, 78% of students occupy a high category and 2% in the low category, while the average skill in the first cycle shows 44.25. In the second cycle there was an increase in the mean score of 47.6 with a very high category presentation of 43%, in the high category there was 57%. Based on the results presented, it prove the use of inquiry learning increase critical thinking skills of 5th grade student of 5th grade of SD Negeri Mangunsari 05 Salatiga